Characterization of the complete plastid genome of Rauvolfia verticillata (Apocynaceae), with its phylogenetic analysis. Issue 2 (3rd July 2019) - Chen, Wenna; Liang, Weiling; Li, An; Ma, Jie
Abstract: Rauvolfia verticillata is a medical plant (Apocynaceae) widely distributed from India to China, the Indo-China Peninsula, Indonesia, and the Philippines. The first complete plastid genome sequence of the species reported here was 155, 856 bp in length, with the large single-copy (LSC) region of 86, 085 bp, the small single-copy (SSC) region of 18, 299 bp, and two inverted repeats (IRa and IRb) of 25, 736 bp. The plastome contained 113 unique genes, including 79 protein-coding genes, 4 ribosomal RNA genes, and 30 transfer RNA genes. The overall GC content was 37.92%. The result from phylogenetic analysis suggests that Rauvolfia is closely related to the genus Catharanthus .